Proceedings of the 17th ACM International Conference on Supporting Group Work 2012
DOI: 10.1145/2389176.2389178
|View full text |Cite
|
Sign up to set email alerts
|

Can a table regulate participation in top level managers' meetings?

Abstract: We present a longitudinal study on the participation regulation effects in the presence of a speech aware interactive table. This study focuses on training meetings of groups of top level managers, whose compositions do not change, in a corporate organization. We show that an effect of balancing participation develops over time. We also report other emerging group-specific features such as interaction patterns and signatures, leadership effects, and behavioral changes between meetings. Finally we collect feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Reithmeier (2013), in the the most recent review of literature mostly produced by HCI and Computer-Supported Cooperative Work research, showed the varied ways in which aspects of faceto-face and distributed group work can be mirrored to promote reflection. In these areas, most of the group visualisations have focused on presenting features of the content of the dialogue between group members Karahalios, 2009a, 2009b) or conversation patterns, not related to the content of the speech, such as speaking time, response patterns and turn taking (DiMicco and Bender, 2004;Kim et al, 2008;Roman et al, 2012). Other visualisations have included information about which person looked at the speaker (Sturm et al, 2007) or the actions of the group members during the activity (Ichino et al, 2009).…”
Section: Visualisation Of Small-group Collaborationmentioning
confidence: 99%
See 3 more Smart Citations
“…Reithmeier (2013), in the the most recent review of literature mostly produced by HCI and Computer-Supported Cooperative Work research, showed the varied ways in which aspects of faceto-face and distributed group work can be mirrored to promote reflection. In these areas, most of the group visualisations have focused on presenting features of the content of the dialogue between group members Karahalios, 2009a, 2009b) or conversation patterns, not related to the content of the speech, such as speaking time, response patterns and turn taking (DiMicco and Bender, 2004;Kim et al, 2008;Roman et al, 2012). Other visualisations have included information about which person looked at the speaker (Sturm et al, 2007) or the actions of the group members during the activity (Ichino et al, 2009).…”
Section: Visualisation Of Small-group Collaborationmentioning
confidence: 99%
“…Previous studies have shown that even quite modest indicators of speech can be effective to describe several aspects of collaboration at non-interactive tabletops (Roman et al, 2012). The automated analysis of speech is an important aspect to analyse collaboration at interactive tabletops but it is still challenging and not yet a mature enough technology to use in collaborative settings (Rosé et al, 2008).…”
Section: Data Capture Foundation (Dcf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Their results suggest that a model for turntaking in conversations is characterized as locally managed, partyadministered, automatically controlled, and sensitive to recipient design. In a meeting scenario, Roman et al presented a longitudinal study on the participation regulation effects on conversations in the presence of a speech awareness interactive table [25]. They showed that an effect of balancing participation develops over time and they reported other emerging groupspecific features such as interaction patterns and signatures, leadership effects, and behavioral changes between meetings.…”
Section: Regulating Participationmentioning
confidence: 99%